THE EFFECT OF SALLACA VINEGAR ON HEMOGLOBIN LEVELS OF MICE (Mus musculus) FEEDED HIGH CHOLESTEROL - Gilang Amanda; Yusni Atifah (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Hemoglobin functions to carry oxygen and circulate throughout body. Several factors affect levels hemoglobin, one of which is food, foods high in cholesterol cause disruption of the quality hemoglobin, this can be overcome by giving Salacca vinegar on a reagular basis to mice that have cholesterol. This study aims to determine the effect of giving Salacca vinegar on Hb levels given high-cholesterol diet. The design used was completely randomized design with 5 treatments (K-: without high-cholesterol diet and SV (Salacca vinegar), K+: given high-cholesterol diet without being given SV, P1: SV 0.8ml, P2: SV 0.4ml and P3 : SV 0.2 ml) with 5 replications. Parameters observed were the Hb levels of male mice before and after being given Salacca vinegar. Data were analyzed using ANOVA, followed by further test of BNT with level of 5%. Results this study indicate that administration Salacca vinegar for 14 days can affect increase in the Hb levels of male mice. The treatment that showed a significant effect was the P3 treatment (SV 0.2ml) because it could increase Hb levels to 17.90 g/dL. Increase Hb levels was due to effect of flavonoids in Salacca vinegar, flavonoids keep haeme ion stable and facilitate production of methemoglobin.